2010
DOI: 10.1007/s00213-010-2040-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cocaine hydrolase on cocaine self-administration under a PR schedule and during extended access (escalation) in rats

Abstract: Rationale and objectives Previously, Albu-CocH, a cocaine hydrolase derived from human butyrylcholinesterase, blocked cocaine-induced reinstatement of drug seeking in rats. In the present study, rats were treated with Albu-CocH while self-administering cocaine under a progressive ratio (PR) schedule during 2-h sessions and under a fixed-ratio 1 (FR 1) schedule during 6-h sessions. Methods In experiment 1, rats were treated with saline or Albu-CocH (2 or 4 mg/kg) before a single 2-h cocaine (0.2 mg/kg) self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…The findings confirm work showing that exogenously administered CocH reduces the physiologic and reinforcing effects of cocaine (e.g., Brimijoin et al, 2008;Carroll et al, 2011). These behavioral effects are achieved by the drastic reduction in the amount of cocaine reaching the brain as a result of CocH activity (Sun et al, 2002a).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings confirm work showing that exogenously administered CocH reduces the physiologic and reinforcing effects of cocaine (e.g., Brimijoin et al, 2008;Carroll et al, 2011). These behavioral effects are achieved by the drastic reduction in the amount of cocaine reaching the brain as a result of CocH activity (Sun et al, 2002a).…”
Section: Discussionsupporting
confidence: 86%
“…A near-optimal enzyme rescued rats from a lethal 100 mg/kg injection of cocaine and blocked cocaine-primed reinstatement, a model of relapse into cocaine-seeking behavior (Brimijoin et al, 2008). Later CocH significantly reduced progressive-ratio responding (i.e., motivation) for intravenous cocaine self-administration (Carroll et al, 2011), suggesting that CocH substantially dampened its reinforcing effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with mutant bacterial CocEs (Brim et al, 2010;Collins et al, 2009) or mutant human BChEs (Carroll et al, 2011) have demonstrated the capacity of highly efficient cocaine-specific hydrolase to inhibit the reinforcing effects of cocaine; however, in each of these studies the inhibitory effects of the enzymes were short-lived, lasting from minutes to hours. The results of the current studies with PEG-CCRQ CocE not only confirm this effect of cocaine-specific esterases, but they also provide convergent evidence that PEG-CCRQ CocE represents a significant improvement over previously described mutant bacterial and human cocaine hydrolases with respect to both the magnitude and duration of its antagonism of the reinforcing effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…These mutant BChEs have shown promising results when evaluated in rodents, effectively reducing the cardiovascular, lethal, and response-reinstating effects of cocaine (Brimijoin et al, 2008;Xue et al, 2010;Zheng et al, 2008). In addition, an albumin-fused mutant BChE (Albu-CocH) has been shown to decrease progressive ratio responding for cocaine (Carroll et al, 2011), suggesting that it is also capable of reducing the reinforcing effectiveness of cocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an antibody can be injected and rapidly block the effect of the drug before it reaches the brain. These effects make antibodies more suitable to treat drug overdose than to extinguish addictive behavior s (Gentry et al, 2010;Zheng & Zhan, 2009;Carroll, Gao, Brimijoin, & Zhan, 2009;Carroll, Gao, Brimijoin, & & Anker, 2011).…”
mentioning
confidence: 99%